Patients\' attitudes and knowledge about drug use: a survey in Turkish family healthcare centres and state hospitals - (:unkn) unknown (My University, 2017)
0

Background/aim: Irrational drug use is a common problem. This study aimed to evaluate patients knowledge and habits concerning drug use, and compare them in terms of some sociodemographic characteristics. Materials and methods: A face-to-face questionnaire was given to outpatients from family healthcare centres (FHCs) and state hospitals (SHs) in 12 provinces in Turkey during May 2010. A total of 4470 patients (FHCs: 2209; SHs: 2261) responded to the questionnaire (response rate: 93.1%). Results: Getting prescriptions without a physical examination was common (second place in FHCs; third place in SHs); 51.0% stated that they wanted physicians to prescribe drugs that they had used before. More than half stated that antibiotics cured every illness. In addition, 55.9% reported that their relatives recommended drugs to them when they got ill; 37.1% reported that they recommended them to relatives as well. Of the survey respondents, 70.5% stated that they had stopped their medications before the recommended time. Patients knowledge and attitudes about drug use showed significant differences in comparisons of sex, age, educational level, and social security. Conclusion: Patients knowledge and attitudes about drugs were far from rational. To eliminate irrational use of drugs, public education about drug use is needed.
Keywords: Cerrahi